(untitled) - Caine, Renate Nummela (Menlo Park, Calif., 1994)
This book by two neuropsychology experts examines how the brain functions during learning experiences and how this knowledge can influence teaching strategies. Grades 1-12
Keywords: Learning,Kiến thức; Physiological aspects,Khía cạnh sinh lý học